Proximate and Mineral Composition of Artocarpus altilis Pulp Flour as Affected by Fermentation - Appiah, F.; Oduro, I.; Ellis, W.O. (Pakistan Journal of Nutrition, 2011)
A study was carried out on to assess the effect of fermentation on proximate composition of Artocarpus altilis pulp flour with the aim of expanding its use. Flours of unfermented and fermented A. altilis pulp were produced and standard procedures used to determine their proximate and mineral composition. Fermentation resulted in marginal increase in crude protein (from 3.80-4.43%) and ash (from 2.37-2.38%) content whereas, there was a marginal decrease in crude fibre (from 3.12-3.00%) and carbohydrate (from 79.24-76.71%) content. Fermentation resulted in significant decrease in calcium, iron, potassium, sodium and phosphorus contents of A. altilis flour. However, magnesium content was not affected by fermentation. This study shows that A. altilis pulp flour has good carbohydrate and mineral content and may therefore, be used as staples, to provide the energy and mineral needs of consumers. They would be useful in ensuring food security if promoted.